Social Determinants, Health Literacy, and Disparities: Intersections and Controversies - Dean Schillinger (SLACK Incorporated, 2021)
This article synthesizes what is known about the relationship between social disadvantage and measures of health literacy (HL), and reviews the research examining whether low HL is an explanatory factor connecting social disadvantage, health outcomes, and health disparities. Written from a United States perspective, this article offers a novel conceptual framework that presents how the social determinants of health might interact with HL to result in health disparities. The framework articulates relationships that reflect public health pathways and health care pathways, which include their related health literacies. The article continues with several cautionary statements based on the inherent limitations of current HL research, including problems and concerns specific to the attribution of HL as an explanatory factor for extant socioeconomic and racial/ethnic health disparities. The article closes with recommendations regarding future research directions. [HLRP: Health Literacy Research and Practice. 2021;5(3):e233-e243.] Plain Language Summary: Socially disadvantaged populations have worse health and health literacy compared to privileged populations. Scientists, health care providers, and policymakers are interested in the possible role health literacy plays in explaining health differences. The article reviews our current understandings of whether and how population characteristics and related exposures to risk interact with low health literacy to generate worse health to inform interventions.